Upaya Pencegahan Perilaku Merokok Pada Siswa SD di Daerah Penghasil Rokok - Ratna Frenty Nurkhalim; Endah Retnani Wismaningsih; Krisnita Dwi Jayanti; Yoanita Indra Kumala Dewi; Reny Nugraheni (Prodi PGSD FIP UNM, 2021)
One of the biggest cigarette producing cities in Indonesia is the City of Kediri. There is a well-known cigarette company in this city, called Gudang Garam. Being in the core area of the cigarette industry makes the community arrouns very familiar with smoking. Smoking is not only enjoyed by adults but also teenagers and children. Smoking has a negative impact, from nicotine addiction to other serious health problems. Therefore, prevention of smoking is especially needed for children and adolescents to avoid the dangers of cigarette smoking. Counseling activities to prevent smoking behavior in children are carried out in Kedak 1 Elementary School, Kediri Regency. The method of community service carried out is by discourse and discussion. Of the 35 counseling participants, there were 15 (43%) children who had smoked. The age of first smoking is 10 years with the number of cigarettes smoked generally as much as 1-2 cigarettes. Before counseling, only 17% of participants had good knowledge about the dangers of smoking. After counseling, the number of participants with good knowledge increased to 31%. To ensure that smoking prevention efforts for children are successful, a structured anti-smoking program needs to be constructed while increasing teacher awareness on anti-smoking issues.